Newly compiled Tai Chi (Bafa Wubu) promotes lower extremity exercise: a preliminary cross sectional study - Li, Haojie; Peng, Fang; Lyu, Shaojun; Ji, Zhongqiu; Li, Xiongfeng; Liu, Mingyu (PeerJ, 2023)
Background Tai Chi (Bafa Wubu) is a new type of simplified Tai Chi widely practiced by Tai Chi enthusiasts that has developed and perfected simplified Tai Chi movement and enriched Tai Chi practice methods. When practicing, Tai Chi athletes and enthusiasts can choose the Bafa Wubu movements to practice according to their physical conditions. The purpose of this article is to discuss the mechanism by which Bafa Wubu promotes lower extremity exercise from the perspective of exercise biomechanics. Objectives This article aims to explore the scientific training methods and technical characteristics of Bafa Wubu, and its contribution to comprehensive exercise of the lower extremities, by analyzing the biomechanical characteristics of the lower extremities of participants who practice Bafa Wubu at different levels and by comparing their ground reaction force, lower limb joints, and muscles during Bafa Wubu. Methods A total of 16 male participants were recruited and divided into an amateur group (N = 8) and a professional group (N = 8). The data were collected by a BTS 3D infrared-based motion capture system, and Kistler 3D force plate. The lower extremity joint forces and muscle strength were calculated by anybody simulation software with inverse dynamics. Results During elbowing and leaning sideways with steps sideways (ELS), the ground reaction force of the professional group was significantly higher than that of the amateur group in the sagittal, vertical, and frontal axes (P < 0.01). While stepping forward, backward, and sideways, the professional group’s joints loading at the hip, knee, and ankle was always higher in the vertical direction (P < 0.01). Furthermore, during warding off with steps forward (WOF), laying with steps forward (LF), and rolling back with steps backward (RBB), hip joint loading increased in the med–lat direction. During actions with steps backward and sideways, the professional group’s ankle flexion/extension torque and hip abduction/rotation torque were significantly larger than those of the amateur group (P < 0.01). Different actions in Bafa Wubu activate muscles to different degrees, whereas the iliacus is mainly responsible for stabilizing postures when practitioners perform standing knee lifting motions. Conclusions Professional groups who have been practicing Tai Chi (Bafa Wubu) for a long time have higher ground reaction force, and the force on the three joints of the lower extremities is different for various movements, which has positive significance for exercising the joints of the lower extremities. In addition, various motions activate muscles of different types at different levels. For amateurs to practice different movements to stimulate the muscles, targeted areas of practice promote the lower extremity muscles’ synergistic force. In summary, the muscles and joints of the lower extremity can obtain comprehensive and balanced exercise through Bafa Wubu.
Keywords: Tai Chi (Bafa Wubu); AnyBody musculoskeletal model; Muscle; Joint; Sport health